Deepwater Horizon Ten Years Later: Regulations, Rollbacks, and Where We Go From Here - James Isacks (Washington University Journal of Law and Policy, 2022)
In 2010, an explosion aboard the oil rig Deepwater Horizon caused approximately 168 million gallons of oil to spill into the Gulf of Mexico—an environmental disaster whose effects are still being felt in the Gulf region. In response to the spill, Congress did not act; instead, the executive branch took the lead, securing a settlement that some predicted would have a deterrent effect on the oil industry and other polluters.The years that have followed since this settlement have consisted of a series of strengthening of regulations under the Obama administration and subsequent weakening by the Trump administration. Immediately upon taking office President Biden signed an executive order directing all agencies to review and consider revising the rules issued during the Trump administration.This Note argues that while we remain in this regulatory limbo, lawmakers and regulators should consider new ways to tackle the ever-looming threat of oil spills and the even larger associated problem of climate change. Isacks argues that more regulation is needed, but regulation is at best a stopgap measure—not to mention one fraught with pushback from powerful interest groups, energy absolutists, and climate change deniers. The Note examines several courses of action before ultimately arguing that the best way to end oil spills is to abandon oil altogether. Isacks concludes that the more lasting solution is to end American dependence on oil and begin the move towards clean, sustainable energy on a federal level.
Keywords: Deepwater; Horizon; Deepwater Horizon; Federal; Executive order; Oil; Oil spills; Renewable energy; Regulation; Agencies; Gulf of Mexico; Pollution; Energy policy; Climate change; Obama; Biden; Trump